Economic Performance and Institutions: Measuring Technical Efficiency Using SPF Approach - Alali, W Y (University of Oxford, 2022)
This paper was created on August 2009 - it was during my MSc study. This paper proposed to employ the SPF approach (stochastic production frontier) to measure the technical efficiency of the country level for best economic performance, as the measure of growth is the essential practice to comprehend the roots of economic growth. It is evident from the results, that there is an essential difference in the perception of the technical efficiency cross-country and the total factor productivity traditional growth measurement. The SPF Model as well allows us to search for technical efficiency sources. The sources of Technical inefficiency cross-country are demonstrated by institutional arrangements. We find amongst all the different measures of institutions the role of openness to international trade, the State and political institutions are important factors of the global economic performance divergence.